Family Parent-Child Woodworking: An Experimental Study on Children Making Luban Locks - Bin Shang; Hui Chen; Ying Hong; Zhe Chen; Jixin Xu (BioResources, 2025)
This study examined the feasibility and benefits of children completing woodworking projects at home in Chinese families, using online video tutorials and parental guidance. A survey assessed family interest and gathered background information, selecting 36 Chinese families with children aged 7 to 12 for an experiment on making traditional Luban locks. The projects were divided into two levels: a basic, video-assisted three-post lock completed by children with parental help; and an advanced, six-post lock, requiring families to find resources independently. Results indicate that the majority of families showed strong interest in parent-child woodworking (76.7%) and successfully completed the basic project (94.4%). However, only a small minority managed to complete the advanced project (8.3%). The study indicates that while children aged 7 to 12 are in a concrete operational stage of cognitive development, success in these projects isn’t solely age-dependent. Parent-child woodworking in Chinese families appears feasible and beneficial for cognitive growth when projects are age-appropriate. Findings suggest designing tasks within a child’s zone of proximal development with corresponding resources, offering insights for family-based learning approaches.